Analisis Manajemen Resiko Pada UMKM Oprit Fried Chiken - Cindi Septian, Yosef; Cindi Firmansyah, Wisnu; Agustina, Bilqis Putri (Jurnal Serambi Ekonomi dan Bisnis, 2024)
The aim of this research is to identify the risk management process, conduct research on risks that may arise and analyze the strategies that will be carried out by MSMEs in handling or managing these risks in the city of Bandung. This research was carried out in accordance with the risk management process (ISO: 31000), namely risk identification, risk analysis, risk evaluation and risk treatment. The risks obtained are the risks that occur most often and are in the high level category in "Oprit Fried Chicken" MSMEs, namely marketing risks and financial risks, namely increases in raw material prices and operational risks, including the absence of SOPs for the use of production machines, human resources who lack understanding in marketing, and expired products. To minimize risks, MSMEs need to identify and then analyze and manage these risks. By implementing effective risk management, "Oprit Fried Chicken" MSMEs can reduce potential losses, increase business resilience amidst business challenges, and take advantage of future growth opportunities. This approach is not only important to maintain business continuity, but also to increase consumer confidence and maintain business reputation in an increasingly competitive culinary market.The increase in prices of basic commodities poses a big challenge for Micro, Small and Medium Enterprises (MSMEs). This price increase can impact the sustainability of MSMEs and pose significant financial risks. This research aims to analyze how the MSME "Oprit Fried Chieken" manages the risks arising from increases in prices of basic commodities. The research methodology includes observation, interviews and statistical data analysis. The research results show that effective risk management helps MSMEs reduce the negative impact of rising prices of basic commodities. This research also provides recommendations for improving risk management in MSMEs and supporting the growth of the MSME sector.